Variation in Forest Structure, Carbon stock and Regeneration status along an Altitudinal Gradient in Jaunpur Range, Mussoorie Forest Division, Uttarakhand - Pandey, Manisha; Joshi, S.P; Sharma, Sachin (Indian Forester, 2025)
The management of forests is essential for the conservation of biodiversity and climate change. The present study aimed to anticipate how forest composition, regeneration, biomass production, and carbon storage vary in the altitudinal gradient in the Jaunpur Range, Mussoorie Forest Division of Garhwal Himalaya. It lies between 30°25.00′–30°33.00’N and 78°3.00’–078°15.00’E and represents a temperate forest. A total of 0.1ha. size 50 sample plots were laid down randomly at each site. Authors recorded 5 different types of forest along the altitudinal gradient. The results reveal that the maximum total biomass for the Pine stand is 198.84 Mgha-1 followed by Oak Stand 70.796 Mgha-1, Moru stand 27.12 Mgha-1, Cedrus stand 22.07 Mgha-1 and minimum 4.39 Mgha-1 for Cupressus stand. All the tree species, 48% showed poor regeneration, 33% showed no regeneration, 5% exhibited new regeneration, 9% represented good regeneration, and the remaining 5% indicated fair regeneration at the study site. Quercus leucotrichophora emerged as the dominant tree species at 1,800–2,000 masl, co-dominant at 1,300–1,500 masl after Pinus roxburghii, showcasing its ability to withstand biotic pressures and exhibit a wider ecological range. The highest tree diversity (H´ = 1.37) was observed at 2000-2200 masl.